2014
DOI: 10.1021/jp409989y
|View full text |Cite
|
Sign up to set email alerts
|

Defect Chemistry of Ceria Nanorods

Abstract: Ceria nanorods were investigated using in situ Raman and FTIR spectroscopies for CO adsorption and subsequent reaction with water at 200 and 350 °C. The involvement of defects in ceria nanorods during CO adsorption and reaction with H 2 O is dependent on the temperature. At 200 °C, most of the carbonate and formate species formed in CO do not involve the formation of defects, while at 350 °C all of the carbonates and formates formed can be correlated to the formation of defects (15% by formates and 85% by mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
87
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 59 publications
6
87
0
Order By: Relevance
“…In particular, two peaks can be resolved at higher Raman shifts, around 580 and 601 cm −1 for CeO 2 and Ce 80 Zr 20 , at 785 nm, which are usually observed as a single convoluted band for more energetic excitation wavelengths [27, 29]. These peaks arise from Frenkel type anion defects, in which an oxygen ion occupies an interstitial position, leaving a vacancy at its original lattice site [31]. A single broad band centered around 567 cm −1 is observed for Pr-doped ceria, which was previously suggested to be the convolution of three contributions due to Pr-induced (~545 and ~570 cm −1 ) and intrinsic oxygen vacancies (~595 cm −1 ) [32].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, two peaks can be resolved at higher Raman shifts, around 580 and 601 cm −1 for CeO 2 and Ce 80 Zr 20 , at 785 nm, which are usually observed as a single convoluted band for more energetic excitation wavelengths [27, 29]. These peaks arise from Frenkel type anion defects, in which an oxygen ion occupies an interstitial position, leaving a vacancy at its original lattice site [31]. A single broad band centered around 567 cm −1 is observed for Pr-doped ceria, which was previously suggested to be the convolution of three contributions due to Pr-induced (~545 and ~570 cm −1 ) and intrinsic oxygen vacancies (~595 cm −1 ) [32].…”
Section: Resultsmentioning
confidence: 99%
“…The first and the third ones can be assigned to the higher order modes of ceria, namely to the second order transverse acoustic mode, that is, 2TA [24] (although a different assignment to a Ce-OH related vibration has recently been suggested [26]), and to the second overtone of the longitudinal optical band (2LO) [26]. The Raman peak at 598 cm −1 is instead a disorder induced mode arising from Frenkel-type anion defects, consisting of a vacancy, originated by the motion of an O 2− ion to an interstitial octahedral site [17,23]. Defect related bands around 550 cm −1 , due to oxygen vacancies at a Ce 3+ site [23], cannot be resolved, thus pointing out that this set of ceria NPs mainly contains oxidized Ce 4+ .…”
Section: Reducibility and Defective Sitesmentioning
confidence: 98%
“…Bands at 540-560 cm -1 and 562 to 599 cm -1 have been assigned to vacancies in doped and pure ceria, respectively [53,54]. Recently, our group suggested that shoulders at 404 and 487 cm -1 arise due to formation of defects, as studied by UV Raman spectroscopy [55]. Without going into the depth, we used Raman spectroscopy as a finger print technique to detect the degree of reduction of catalysts after EB dehydrogenation.…”
Section: Characterization Of the Spent Ceria Catalysts With Raman Spementioning
confidence: 99%